2009
DOI: 10.1118/1.3121511
|View full text |Cite
|
Sign up to set email alerts
|

CADx of mammographic masses and clustered microcalcifications: A review

Abstract: Breast cancer is the most common type of cancer among women in the western world. While mammography is regarded as the most effective tool for the detection and diagnosis of breast cancer, the interpretation of mammograms is a difficult and error-prone task. Hence, computer aids have been developed that assist the radiologist in the interpretation of mammograms. Computer-aided detection (CADe) systems address the problem that radiologists often miss signs of cancers that are retrospectively visible in mammogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(109 citation statements)
references
References 161 publications
(241 reference statements)
1
108
0
Order By: Relevance
“…Generally, a heuristic optimization technique does not guarantee an optimal solution in most cases. However, such approaches is still more attractable than analytical one because a heuristic search can escape from local minima [2], produce a near optimal solution, and perform very well even when search space is very large. Several studies have reported the efficacy of PSO over GAs and other evolutionary algorithms.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, a heuristic optimization technique does not guarantee an optimal solution in most cases. However, such approaches is still more attractable than analytical one because a heuristic search can escape from local minima [2], produce a near optimal solution, and perform very well even when search space is very large. Several studies have reported the efficacy of PSO over GAs and other evolutionary algorithms.…”
Section: Particle Swarm Optimizationmentioning
confidence: 99%
“…Presence of MCs is a key to an early detection and diagnosis of breast cancer. These challenges and the nature of MCs lead to unsatisfactory positive predictive value (PPV) of mammography-based breast cancer diagnosis [1]- [2]. Hence, computer aided diagnosis (CADx) technology is very crucial to assist radiologist in reading mammogram, improving the PPV of mammography by providing radiologist with second opinion when double reading stage is not feasible most of the time [1].…”
Section: Introductionmentioning
confidence: 99%
“…The two template sizes together with three resolutions give a total of six various relations between the mammogram and the template. It is shown in [22] that the smallest template should have the radius equal to 4 ffiffi ffi 2 p R min ; where R min is the radius in pixels of the smallest mass to be detected.…”
Section: Mass Detectormentioning
confidence: 99%
“…There is a wealth of ideas, concepts, and research results, as exemplified by four review papers recently published [1][2][3][4]. Various algorithms have been proposed and even their classification is a matter of personal experience and preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation